Prospective evaluation of digital single‐operator cholangioscope for diagnostic and therapeutic procedures (with videos). Issue 7 (4th May 2017) - Ogura, Takeshi; Imanishi, Miyuki; Kurisu, Yoshitaka; Onda, Saori; Sano, Tastsushi; Takagi, Wataru; Okuda, Atsushi; Miyano, Akira; Amano, Mio; Nishioka, Nobu; Yamada, Tadahiro; Masuda, Daisuke; et al.
Abstract : Background and Aim: Recently, the digital single‐operator cholangioscope (SPY‐DS) has become available. This system may allow diagnosis by direct visualization and allow performance of various therapeutic procedures. The aim of the present study was to prospectively evaluate the clinical utility of DSOCS for diagnostic and therapeutic procedures for biliary disease. Methods: Technical success was defined as successful visualization of target lesions in the biliary tract and carrying out forceps biopsy as a diagnostic procedure, and successfully carrying out treatment such as guidewire insertion for the area of interest, electrohydraulic lithotripsy (EHL), or migrated stent removal. Also, the present study aimed at investigating diagnostic yield of the cholangioscopic findings and biopsy specimens. Results: A total of 55 consecutive patients were prospectively enrolled in this study; a diagnostic procedure was done in 33 patients, and a therapeutic procedure was done in 22 patients. Overall accuracy of visual findings was 93%, with a sensitivity of 83%, a specificity of 89%, positive predictive value (PPV) of 83%, and negative predictive value (NPV) of 100%. However, the overall accuracy of forceps biopsy was 89%, with a sensitivity, specificity, and PPV of 100%, and NPV of 90%. Overall technical success rate of therapeutic procedures such as selective guidewire insertion, EHL or migrated stent removal was 91% (20/22). Finally, adverse events were seen in two cases in the diagnostic group, but were not seen in the therapeutic group. Conclusion: Although additional cases and a randomized, controlled study with another cholangioscope are needed, diagnostic and therapeutic procedures using SPY‐DS appear to be feasible and safe.